2017
DOI: 10.1186/s13643-017-0587-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra-pregnancy nonsurgical periodontal therapy on inflammatory biomarkers and adverse pregnancy outcomes: a systematic review with meta-analysis

Abstract: BackgroundThe aim of this systematic review with meta-analysis was to analyze the effects of intra-pregnancy nonsurgical periodontal therapy on periodontal inflammatory biomarkers and adverse pregnancy outcomes.MethodsOn June 5, 2017, we searched PubMed, Cochrane, SCOPUS, Web of Science, LILACS, ProQuest, Open Grey, and Google Scholar databases. Randomized clinical trials in which pregnant women with chronic periodontitis underwent nonsurgical periodontal therapy, compared with an untreated group, tested for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 38 publications
0
32
0
3
Order By: Relevance
“…Though some reports found efficacy of periodontal treatment during pregnancy in a high‐risk group mothers, most of the studies concluded that the treatment of periodontal diseases could not reduce the incidence of APO . According to a systematic review with meta‐analysis, nonsurgical periodontal therapy during pregnancy improved periodontal clinical findings; however, it did not reduce PTB or LBW . Another systematic review and meta‐analysis also concluded that treatment of periodontal diseases with scaling and root planing did not reduce the incidence of PTB (OR 1.15, 95% CI 0.95–1.40), LBW (OR 1.07, 95% CI 0.85–1.36) or spontaneous abortions/stillbirths (OR 0.79, 95% CI 0.51–1.22) .…”
Section: Epidemiological Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though some reports found efficacy of periodontal treatment during pregnancy in a high‐risk group mothers, most of the studies concluded that the treatment of periodontal diseases could not reduce the incidence of APO . According to a systematic review with meta‐analysis, nonsurgical periodontal therapy during pregnancy improved periodontal clinical findings; however, it did not reduce PTB or LBW . Another systematic review and meta‐analysis also concluded that treatment of periodontal diseases with scaling and root planing did not reduce the incidence of PTB (OR 1.15, 95% CI 0.95–1.40), LBW (OR 1.07, 95% CI 0.85–1.36) or spontaneous abortions/stillbirths (OR 0.79, 95% CI 0.51–1.22) .…”
Section: Epidemiological Resultsmentioning
confidence: 99%
“…Since multiple factors, that is, maternal age, body weight, past history, smoking, obstetric history and socioeconomic factors, are associated with the incidence of APO, the analysis should be carefully designed. Another concern is that the definitions of periodontal diseases have varied depending on previous studies . To elucidate the causation of periodontal diseases on APO incidence, randomized clinical trials and widely accepted diagnostic criteria for periodontal diseases that are of high methodological quality are needed.…”
Section: Epidemiological Resultsmentioning
confidence: 99%
“…Além disto, há consenso dos artigos apresentados de que há grande importância da atuação do Cirurgião-Dentista na gestante, pois as doenças orais, como a gengivite e periodontite, podem levar bactérias a nível sistêmico ou mesmo pode haver transmissibilidade vertical de doenças, como no caso da cárie e também dos patógenos das doenças periodontais (KLOETZEL et al, 2011;STEINBERG et al, 2013;BOUTIGNY et al, 2016;HARTNETT et al, 2016;SILVA et al, 2017;MARLA et al, 2018;POMINI et al, 2018). Embora haja na literatura a correlação do estado periodontal das pacientes e resultados adversos da gravidez, este ainda é considerado um assunto controverso, necessitando de estudos posteriores (BOUTIGNY et al, 2016;KOMINE-AIZAWA et al, 2018).…”
Section: Discussionunclassified
“…Episódios frequentes de bacteremia ou disseminação de endotoxinas bacterianas do foco periodontal podem induzir a ativação sistêmica da resposta inflamatória e intensa produção de citocinas pró-inflamatórias. Desta forma, o trânsito sistêmico de patógenos periodontais, citocinas pró-inflamatórias e prostaglandinas das bolsas periodontais para a unidade fetoplacentária corrobora com uma hipótese plausível para a associação entre doença periodontal e complicações da gravidez, como partos prematuros e baixo peso ao nascer (SILVA et al, 2017).…”
Section: A Influência Da Condição Oral Na Saúde Da Gestante E Do Bebêunclassified
See 1 more Smart Citation